Revisiting cancer 15 years later: Exploring mortality among agricultural and non‐agricultural workers in the Serrana Region of Rio de Janeiro. Issue 1 (4th October 2016) - Krawczyk, Noa; de Souza Espíndola Santos, Aline; Lima, Jaime; Meyer, Armando
Abstract : Background Agricultural production has expanded dramatically throughout Brazil. Previous research in the Serrana Region found that from 1979 to 1998, agricultural workers experienced high mortality rates from certain cancers compared to non‐agricultural workers [Meyer et al. (2003): Environ Res 93:264–271]. Methods: New data were obtained for 1999–2013 and Mortality Odds Ratios (MORs) were utilized to compare cancer and other mortality between male agricultural workers in the Serrana Region and non‐agricultural workers in the Serrana Region, Rio de Janeiro, and Porto Alegre, and to compare mortality odds to previous decades. Results: Respectively, compared to aforementioned reference‐groups, agricultural workers experienced highest MORs for stomach (1.55 [95%CI: 1.13–2.12], 2.30 [95%CI: 1.72–3.08], 2.28 [95%CI: 1.69–3.08]) and esophageal cancers (95%CI: 1.93 [1.38–2.7], 1.93 [95%CI: 1.38–2.71], 3.12 [95%CI: 2.30–4.24]), greater than reported in previous decades. Agricultural workers experienced higher mortality for external‐causes, respiratory, and cardiovascular problems compared to urban reference‐groups. Conclusion: Agricultural workers may be at increasing risk for cancer and other mortality. Efforts are needed to investigate distinct risk‐factors among this group. Am. J. Ind. Med. 60:77–86, 2017. © 2016 Wiley Periodicals, Inc.